Analisis Prediksi Kata Kunci Situs Web MonsterMAC dengan Metode Long Short-Term Memory (LSTM) - Hanif Assalmi, Fityan; Syaifullah Jauharis Saputra, Wahyu; Muhaimin, Amri (Jurnal Teknologi Terpadu, 2024)
Amid increasingly fierce competition in the digital realm, many companies are striving to increase the number of visitors to their websites. One such competing company is MonsterMAC, a startup. This research aims to provide early warnings and analyze relevant keywords on the MonsterMAC website using the Long Short-Term Memory (LSTM) method. Visitor data from Google Analytics and keyword data from Google Trends for the period July 22, 2022, to July 15, 2023, have been collected and processed through several stages, such as preprocessing, model design, LSTM training, and testing, as well as visualization and interpretation of results. The modeling results show satisfactory performance, with MAE Train Real User = 0.0615, Vending Machine = 0.0218, IoT = 0.0284, Machine Learning = 0.0365, Digital Business = 0.0186, Business Intelligence = 0.0296. Furthermore, this research indicates that the number of visitors is predicted to increase but will also experience a sharp decline in the coming days. The use of the keyword "IoT" shows a significant increasing trend. Implementing the keyword "IoT" in SEO strategies has increased the number of visitors over the next seven days from 250 to 350. This research guides website owners in optimizing their content and SEO strategies to increase their visibility and competitiveness in a highly competitive digital environment. This research also emphasizes the importance of the LSTM method in keyword analysis and prediction to create more targeted SEO strategies.